2008
DOI: 10.1111/j.1559-1816.2008.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Situationally Induced State Goal Orientation Effects on Task Perceptions, Performance, and Satisfaction: A Two‐Dimensional Conceptualization1

Abstract: We examined the longitudinal effects of situationally induced 2-dimensional state goal orientations (i.e., achievement goals) on perceptions, performance, and satisfaction. Results (N = 268) indicated that high state learning cues led to higher perceived challenge and, for higher ability individuals, greater performance gains. Further, high state performance cues led to higher perceived effort. However, results revealed that state learning and performance effects were more complex than expected. State learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
(65 reference statements)
3
24
2
Order By: Relevance
“…Our findings indicated that in different situations, approach performance played different roles in determining creative performance. Many scholars have agreed that performance orientation motivates employees to work hard (Steele-Johnson, Heintz, & Miller, 2008;Lu, Lin, & Leung, 2012), which may not necessarily lead to higher creativity (Hirst, van Knippenberg, & Zhou, 2009). Surprisingly, we found that avoidance performance orientation was significantly related to employee creativity, which is not consistent with the findings of previous studies conducted in workplace settings (Hirst, van Knippenberg, & Zhou, 2009).…”
Section: Contributions To Scholarshipcontrasting
confidence: 68%
See 1 more Smart Citation
“…Our findings indicated that in different situations, approach performance played different roles in determining creative performance. Many scholars have agreed that performance orientation motivates employees to work hard (Steele-Johnson, Heintz, & Miller, 2008;Lu, Lin, & Leung, 2012), which may not necessarily lead to higher creativity (Hirst, van Knippenberg, & Zhou, 2009). Surprisingly, we found that avoidance performance orientation was significantly related to employee creativity, which is not consistent with the findings of previous studies conducted in workplace settings (Hirst, van Knippenberg, & Zhou, 2009).…”
Section: Contributions To Scholarshipcontrasting
confidence: 68%
“…Many scholars have recognized that performance orientation motivates employees to work hard (Steele-Johnson, Heintz, & Miller, 2008;Lu, Lin, & Leung, 2012), which may not necessarily lead to higher creativity (Hirst, van Knippenberg, & Zhou, 2009). Surprisingly, we found that avoidance performance orientation was significantly related to employee creativity, indicating that under some circumstances avoidance performance orientation can enhance employee creativity (Baas, De Dreu, & Nijstad, 2011;Roskes, De Dreu, & Nijstad, 2012).…”
Section: Contributions To Scholarshipcontrasting
confidence: 66%
“…While trait PGO may not be amenable to change, it may be possible to reduce the transient activation of state PGO in specific situations by reducing task importance as mentioned above, emphasizing self assessment against one's own goals, and minimizing the use of comparative feedback and evaluation by or against others (Steele-Johnson et al, 2008;Tyson et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Information on task importance has occasionally been used in laboratory studies as part of a manipulation to induce state performance goals (e.g. Steele-Johnson, Heintz, & Miller, 2008). A stronger transient state of performance orientation should further heighten negative and dampen positive emotions.…”
Section: Performance Goal Orientation Emotions and Appraisalsmentioning
confidence: 99%
“…Future research may attempt to develop traitlike and state-like versions of these scales, in line with similar constructs such as learning goal orientation (Steele-Johnson, Heintz, & Miller, 2008). These measures could help to clarify whether some individuals are more inclined than others to focus on either their strengths or their deficits across a broad range of situations.…”
Section: Limitations and Future Researchmentioning
confidence: 99%